Literasi Matematis Peserta Didik SMP Tipe AQ Climber dalam Menyelesaikan Soal PISA Konten Bilangan Ditinjau dari Jenis Kelamin - Ayu Widya Khusnulkhotimah; Abdul Haris Rosyidi (MATHEdunesa, 2026)
Mathematical literacy involves the processes of formulating, employing, and interpreting to solve real-life problems. However, students' mathematical literacy skills, particularly in the quantity content of the PISA, remain low, indicating difficulties in understanding information and integrating mathematical concepts into real-life contexts. Furthermore, differences in students' persistence in solving these problems suggest that Adversity Quotient (AQ) plays an important role in understanding students’ mathematical literacy. Climber-type are optimistic, persistent, and strive to solve problems thoroughly. These characteristics are in line with the demands of PISA problems that are complex and contextual, requiring high-level reasoning. This study aims to describe the mathematical literacy of junior high school students in solving PISA problems in the Quantity content based on the AQ category (Climber) and gender (male and female). This study employed a case study approach involving two students. Data were obtained through the Adversity Response Profile questionnaire, mathematical literacy tests, and interviews, then analyzed through condensation, presentation, and drawing conclusions. The results showed that in the formulating stage, male and female students identified mathematical elements and determined a mathematical model. In the employing stage, male students used the strategy of equating the price. Meanwhile, female students used the strategy of dividing the area by the price. In the interpreting stage, male students reinterpreted the calculation results into the context of the problem and explained the results in a reasonable way. Meanwhile, female students did not reinterpret the calculation results into the context of the problem correctly and did not explain the results in a reasonable way. Therefore, it is recommended that teachers provide scaffolding to help students, especially those who experience difficulties at the interpretation stage, and further research is expected to be able to examine in more depth the factors that influence these difficulties.